Cambridge Integrated Knowledge Centre Sponsorship - Keivanidis, Panagiotis E. (My University, 2026)
Sponsorship offered by the Cambridge Integrated Knowledge Centre in Advanced Manufacturing Technologies and Electronics (CIKC), Optoelectronics Group, Cavendish Laboratory, Department of Physics, University of Cambridge, Cambridge (UK)
Keywords: Natural sciences